Exploring subregional conflict : (Lynne Rienner Publishers, 2004)
The causes of violent conflict, as well as approaches to conflict prevention, have been studied extensively, but only recently has attention been given to the subregional dynamics of internal wars. The authors of this original collection explore conflicts in Africa, Central Asia, and Central America, seeking new insights that can provide the foundation for more nuanced, more effective preventive strategies.